1989
DOI: 10.1111/j.1365-2184.1989.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

The cell kinetics of the epidermis and follicular epithelium of the rat: variations with age and body site

Abstract: The skin from rats of differing age was used to quantify variations in the cell kinetics of the epidermis and the follicular epithelium of different body sites. Four parameters were assessed, namely the basal cell density (BCD), the labelling index (LI), the duration of DNA synthesis (ts) and the basal cell turnover time (tT). The BCDs of the epidermis of the dorsum and the upper surface of the foot were similar in rats of 7, 14 and 52 weeks of age, but there was an indication of a progressive decline with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
6
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
4
6
0
1
Order By: Relevance
“…The present results are in keeping with earlier findings (Morris et al, 1989) where it was shown that there was a progressive decline in the rates of cell proliferation, in a variety of body sites, with age in the rat. The changes in the rates of cell proliferation appeared to be associated with age-related changes in the growth of those body sites (Morris eta]., 1989).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present results are in keeping with earlier findings (Morris et al, 1989) where it was shown that there was a progressive decline in the rates of cell proliferation, in a variety of body sites, with age in the rat. The changes in the rates of cell proliferation appeared to be associated with age-related changes in the growth of those body sites (Morris eta]., 1989).…”
Section: Discussionsupporting
confidence: 93%
“…for the same region obtained using a double labelling technique (Morris et al, 1989) and than the values of 9-11 h suggested by the present single pulse LI data. The discrepancy in these estimates of Ts may be due to the effects of diurnal variation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations